A Comparative Study of Two Different Taste Masking Approaches for Taste Masking of Azithromycin - Upadhye, Kanchan P. (Asian Journal of Pharmaceutics (AJP), 2022)
Objective: Azithromycin is a BCS Class II drug having a poor water solubility and bitter taste, which leads to poor patient compliance, especially in paediatric and geriatric patients. Thus in the present work taste masking was done using two methods, solid dispersion (SD) and complexation using ion exchange resin and the two methods were compared with respect to their efficiency of taste masking. Methodology: In this research work, SDs were prepared by solvent evaporation method using ethanol as a solvent. Furthermore, drug resin complex containing indion 234, a weak cation exchange resin was prepared by batch method. Both, SDs and drug resin complexes were evaluated by FTIR, SEM, PXRD, and DSC studies and with respect to their micromeritic properties, solubility, drug content, dissolution, and taste evaluation. Results and Discussion: The study showed that both the SDs as well as drug resin complex showed improvement in taste as well as physicochemical properties, The drug content and % drug release of the optimized batch prepared by SD method was found to be more that is 92.56 Â± 0.75% and 96.77%, respectively for SD5 (1:0.75) as compared to the optimized batch prepared by the ion exchange resin that is 67.52 Â± 0.51% and 75.25% for DRC4 (1:4).Taste evaluation studies also revealed a better taste masking with SD as compared to drug resin complex. Thus, it can be concluded that due to its versatile utility SD method was found to be the best and more efficient as compared to the ion exchange resin method for taste making of bitter tasting drugs.